Risk Assessment of Boot Hydropower Projects in Nepal Using Fuzzy Logic Approach - Tripathi, Pramesh; Shrestha, Santosh Kumar (Journal of Advanced College of Engineering and Management, 2018)
Many Hydropower Projects in Nepal are carried out with insufficient risk assessment because of which time over run or variations are predominant. Many projects are stuck in preconstruction phase and others in construction phase. In this study all possible risks associated with the BOOT Hydropower Project in Nepal were identified and evaluated. Fuzzy rating tool has been used to quantify the risk associated with the BOOT Hydropower Projects in Nepal. It provides a flexible and easily understood way to analyze the project risks. The relative importance (impact) of risk factors was determined from the survey results. A set of questionnaire was prepared for the survey. The survey was conducted with the experts that have experience in BOOT hydropower projects. From the survey, among the type of risks, Grid Connection / Power Evacuation, Political risk and Geological risk were found to be predominant risk respectively in BOOT hydropower projects in Nepal. The risk assessment method enabled a Risk Index (R) value to be calculated, establishing a 4-grade evaluation system: low risk having R values between 1.17 and 1.69; medium risk, between 1.69 and 2.08; high risk, between 2.08 and 2.47; extreme risk, between 2.47 and 2.78. Applicability of the methodology was tested on a real case hydropower project namely Middle Modi Hydroelectric Project (15.1 MW) which is in construction phase on Modi River in Western Region in Nepal and Madhya Bhotekosi Jalavidyut Company Ltd. (102 MW) which is also in construction phase on Bhotekoshi River in Central Region in Nepal. The risk analysis method will give investors a more rational basis on which to make decisions and it can prevent cost and schedule overruns. An overall risk index can be used as early indicators of project problems or potential difficulties. Evaluators can keep track to evaluate the current risk level with the progress of investments. Journal of Advanced College of Engineering and Management, Vol. 3, 2017, Page: 115-125